High-Speed Computation using FPGA for Excellent Performance of Direct Torque Control of Induction Machines - Tole Sutikno; Nik Rumzi Nik Idris; Auzani Jidin (Universitas Ahmad Dahlan, 2016)
The major problems in hysteresis-based DTC are high torque ripple and variable switching frequency. In order to minimize the torque ripple, high sampling time and fast digital realization should be applied. The high sampling and fast digital realization time can be achieved by utilizing high-speed processor where the operation of the discrete hysteresis regulator is becoming similar to the operation of analog-based comparator. This can be achieved by utilizing field programmable gate array (FPGA) which can perform a sampling at a very high speed, compared to the fact that developing an ASIC chip is expensive and laborious.